Expectations of Care, Perceived Safety, and Anxiety following Acute Behavioural Disturbance in the Emergency Department - Magdalen Lim; Tracey Weiland; Marie Gerdtz; Andrew Dent (Emergency Medicine International)
Objective. We explored perspectives of emergency department users (patients and visitors) regarding the management of acute behavioural disturbances in the emergency department and whether these disturbances influenced their levels of anxiety. Methods. Emergency department patients and visitors were surveyed using the State-Trait Anxiety Inventory, and a purpose-designed questionnaire and semistructured interview. The main outcome measures were themes that emerged from the questionnaires, the interviews, and scores from the state component of the State-Trait Anxiety Inventory. Results. 70 participants were recruited. Users of the emergency department preferred behaviourally disturbed people be managed in a separate area from the general emergency department population so that the disturbance was inaudible (𝑛=32) and out of view (𝑛=40). The state anxiety levels of those that witnessed an acute behavioural disturbance were within the normal range and did not differ to that of ED patients that were not present during such a disturbance (median, control = 37, Code Grey = 33). Conclusions. Behavioural disturbances in the emergency department do not provoke anxiety in other users. However, there is a preference that such disturbances be managed out of visual and audible range. Innovative design features may be required to achieve this.